Resilience And Social Support As Predictors Of Work Engagement In Employees At Pt. X - Agatha T Veronica Tampombebu (Green Publisher Indonesia, 2025)
This study aims to examine the role of resilience and social support as predictors of work engagement among employees of PT. X, a labor outsourcing company in North Morowali, Central Sulawesi. Work engagement refers to employees’ positive attachment to their work, encompassing vigor, dedication, and absorption. Resilience is defined as the ability to adapt and persevere in the face of challenges, while social support includes emotional, informational, and material assistance from the surrounding environment. This research employed a quantitative approach with a multiple linear regression design. The sample consisted of all 100 employees of PT. X, selected using a saturated sampling technique. Data were collected using the Resilience Scale (Wagnild & Young), the Social Support Scale (Cohen et al.), and the Utrecht Work Engagement Scale (Schaufeli & Bakker). The results indicate that resilience and social support simultaneously have a significant effect on work engagement (R² = 0.425; p < 0.05), with effective contributions of 22.32% and 20.19%, respectively. Partially, both variables were also significant predictors of work engagement. These findings highlight that the combination of internal strength (resilience) and external resources (social support) enhances employees’ engagement at work. The study provides insights for management to develop programs that strengthen resilience and social support to optimize employee performance.